Synthesis and Properties of Amphiphilic Photoresponsive Gelators for Aromatic Solvents - Rajaganesh, Ramanathan; Gopal, Anesh; Mohan Das, Thangamuthu; Ajayaghosh, Ayyappanpillai (Organic letters, 2012)
A sugar-based photoresponsive supergelator, N-glycosylazobenzene that shows selective gelation of aromatic solvents is described. The partial trans–cis isomerization of the azobenzene moiety allows photoinduced chopping of the entangled gel fibers to short fibers, resulting in controlled fiber length and gel–sol transition. The gelator is useful for the selective removal of toxic aromatic solvents from water.